2020
DOI: 10.1002/adbi.202000094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen and Glucose on Bone Marrow Mesenchymal Stem Cell Culture

Abstract: including skin, bone, cartilage, heart tissues, blood vessels, etc., have successfully been recreated in vitro, [3-5] their clinical application is limited. Most tissues are highly vulnerable to ischemia, [6] hindering the survival of clinically relevant tissue volumes after implantation in vivo of engineered constructs. The inability to deliver oxygen and nutrients to cells within scaffolds is thought to result in cell death and lack of efficiency of transplanted cells. [7-9] Indeed, oxygen and nutrient suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Studies reveal that BMSCs have great potential for alleviating POF in laboratory-based investigations and pre-clinical as well as clinical studies in the last decade ( 64 , 201 , 202 ). BMSCs transplantation is a terrific option for POF treatment due to their low immunogenicity, availability and broad sources ( 35 , 37 ). They can improve POF ovarian function through various mechanisms including paracrine, angiogenesis, anti-fibrosis, anti-inflammatory and immune regulation, anti-oxidative stress, inhibition of apoptosis, mitochondrial transfer and autophagy regulation after homing to the damaged ovary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reveal that BMSCs have great potential for alleviating POF in laboratory-based investigations and pre-clinical as well as clinical studies in the last decade ( 64 , 201 , 202 ). BMSCs transplantation is a terrific option for POF treatment due to their low immunogenicity, availability and broad sources ( 35 , 37 ). They can improve POF ovarian function through various mechanisms including paracrine, angiogenesis, anti-fibrosis, anti-inflammatory and immune regulation, anti-oxidative stress, inhibition of apoptosis, mitochondrial transfer and autophagy regulation after homing to the damaged ovary.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depending on the source, the immunophenotypic and secretome vary from different MSCs that accounts for some differences in their responses ( 33 , 34 ). BMSCs have been widely used due to their great potential of proliferation and multidirectional differentiation as well as stable genetic background ( 35 38 ). Recent studies also confirmed that BMSCs have shown remarkable therapeutic effects in many diseases including hematopoietic diseases, musculoskeletal diseases, immune disorders, neurodegenerative diseases, cardiovascular diseases, sports injuries, gastrointestinal and cutaneous diseases as well as POF ( 39 44 ).…”
Section: Biological Characteristics Of Bmscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, glucose uptake rate considerably changes the growth rate, which is in line with the recently published observations. [ 10 ]…”
mentioning
confidence: 99%